Development of Students Worksheet Chemical Bond Based On Learning Cycle 7E - Utari Oktavianti; Asmadi M. Noer; Lenny Anwar S (EduChemia (Jurnal Kimia dan Pendidikan), 2020)
This development research aims to produce worksheet chemical bonds based on Learning Cycle 7E,  to know the validity level of the worksheet according to the validators, to know the practicality level of the worksheet according to the teacher, and to know the attractiveness level of the worksheet according to students. The development model follows the plomp model. Plomp consists of the preliminary investigation phase, the design phase, realization or construction phase, the test phase, evaluation and revision, and the implementation phase. Based on the results of product validation by three validators, the results obtained with the category valid from five aspects, namely the feasibility of the content, Learning Cycle 7E characteristics, language, presentation, and graphics with the percentage of 91.67%, 92.71%, 94.44%, 91.66%, and 88.89%. Teachers 'response as worksheet users based on the Learning Cycle 7E category is very practical with a percentage of 88.15%, and students' responses to worksheet based on the Learning Cycle 7E category are very interesting with a percentage of 89.99%.